Effect of Hepatic Impairment on OATP1B Activity: Quantitative Pharmacokinetic Analysis of Endogenous Biomarker and Substrate Drugs. Issue 5 (15th January 2023) - Lin, Jian; Kimoto, Emi; Yamazaki, Shinji; Vourvahis, Manoli; Bergman, Arthur; Rodrigues, A. David; Costales, Chester; Li, Rui; Varma, Manthena V. S.
Abstract : Hepatic impairment (HI) is known to modulate drug disposition and may lead to elevated plasma exposure. The aim of this study was to quantitate the in vivo OATP1B‐mediated hepatic uptake activity in populations with varying degrees of HI. First, we measured baseline levels of plasma coproporphyrin‐I, an endogenous OATP1B biomarker, in an open‐label, parallel cohort study in adult subjects with normal liver function and mild, moderate, and severe HI ( n  = 24, 6/cohort). The geometric mean plasma concentrations of coproporphyrin‐I were 1.66‐fold, 2.81‐fold ( P  < 0.05), and 7.78‐fold ( P  < 0.0001) higher in mild, moderate, and severe impairment than those healthy controls. Second, we developed a dataset of 21 OATP1B substrate drugs with HI data extracted from literature. Median disease‐to‐healthy plasma area under the curve (AUC) ratios for substrate drugs were ~ 1.4, 3.0, and 6.4 for mild, moderate, and severe HI, respectively. Additionally, significant linear relationship was noted between AUC ratios of substrate drugs without and with co‐administration of rifampin, a prototypic OATP1B inhibitor, and AUC ratios in moderate ( P  < 0.01) and severe ( P  < 0.001) HI. Third, a physiologically‐based pharmacokinetic model analysis was conducted with 10 substrate drugs following estimation of relative OATP1B functional activity in virtual disease population models using coproporphyrin‐I data and verification of substrate models with rifampin drug–drug interaction data. This approach adequately predicted plasma AUC change particularly in moderate (9 of 10 within 2‐fold) and severe (5 of 5 within 2‐fold) HI. Collective findings indicate progressive reduction, by as much as 90–92%, in OATP1B activity in the HI population.